Efficacy of individual computer-based auditory training for people with hearing loss: a systematic review of the evidence - Henshaw, Helen; Ferguson, Melanie (Public Library of Science, 2013)
Auditory training involves active listening to auditory stimuli and aims to improve performance in auditory tasks. As such, auditory training is a potential intervention for the management of people with hearing loss.